SASTRA CYBER DI INDONESIA - Fitriani, Laily (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2007)
The digital era started when the internet technology spread to the developing countries including Indonesia. The flourish of cyber literature leads to the debate on the quality of the work of literature. Above all, the existence of literature sites (cyber literature) becomes an important alternative for writers and literary activist in Indonesia.